Reshaping of Gait Coordination by Robotic Intervention in Myelopathy Patients After Surgery - Puentes, Sandra; Kadone, Hideki; Kubota, Shigeki; Abe, Tetsuya; Shimizu, Yukiyo; Marushima, Aiki; Sankai, Yoshiyuki; Yamazaki, Masashi; Suzuki, Kenji (Frontiers in Neuroscience, 2018)
The Ossification of the Posterior Longitudinal Ligament (OPLL) is an idiopathic degenerative spinal disease which may cause motor deficit. For patients presenting myelopathy or severe stenosis, surgical decompression is the treatment of choice; however, despite adequate decompression residual motor impairment is found in some cases. After surgery, there is no therapeutic approach available for this population. The Hybrid Assistive Limb® (HAL) robot suit is a unique powered exoskeleton designed to predict, support and enhance the lower extremities performance of patients using their own bioelectric signals. This approach has been used for spinal cord injury and stroke patients where the walking performance improved. However, there is no available data about gait kinematics evaluation after HAL therapy. Here we analyze the effect of HAL therapy in OPLL patients in acute and chronic stages after decompression surgery. We found that HAL therapy improved the walking performance for both groups. Interestingly, kinematics evaluation by the analysis of the elevation angles of the thigh, shank and foot by using a principal component analysis showed that planar covariation, plane orientation and movement range evaluation improved for acute patients suggesting an improvement in gait coordination. Being the first study performing kinematics analysis after HAL therapy, our results suggest that HAL improved the gait coordination of acute patients by supporting the relearning process and therefore reshaping their gait pattern.